The Effect of Indonesian Government Rationalization Policy on the Investment Feasibility of the Solo-Mantingan-Ngawi Toll Road - Hermawan , Ribut (International Journal of Psychosocial Rehabilitation, 2020)
The government policy to reduce rates for the Solo-Mantingan-Ngawi toll road from Rp 1,300/km to Rp 1,000/km was stipulated in the Decree of the Minister of Public Works and Public Housing Number: 56/KPTS/M/2019 on January 14, 2019. This decree concerns the determination of motor vehicle classes and toll rates on the Solo-Mantingan-Ngawi Toll Road. This study analyzed the relationship between government policy for determining toll rates and its effect on investment feasibility.The analysis revealed that by changing toll rates, the investment feasibility of the Solo-Mantingan-Ngawi toll road was adversely affected. The Internal Rate of Return (IRR) value decreased from 15.73% to 13.58%, and the Net Present Value (NPV) decreased from Rp 5,495,247 million to Rp 1,357,181 million, with a cash flow deficit that increased from Rp 3 trillion to Rp 10.38 trillion. The payback period also increased from 14 years 5 months to 15 years. A review of the literature regarding the applicable rules revealed that the Indonesian government policy of reducing the Solo-Mantingan-Ngawi toll rate from Rp 1,300/km to Rp 1,000/km significantly affected the investment feasibility of the Solo-MantinganNgawi toll road. This policy reduced the initial cash flow for business entities involved in the project as they experienced a large cash deficit. By understanding the conceptual model, this study provided insights into the effects of government policy, especially in determining the Solo-Mantingan-Ngawi toll road rate and the investment feasibility of the toll road. Additionally, the conceptual model developed in this study is expected to provide an overview of the application of government policy for toll road investment businesses and other fields of investment.